(untitled) (LEARNing Landscapes, 2013)
To understand the kindergarten of today, it is important to comprehend early childhood education of the past. This article surveys the evolution of childhood and of the kindergarten from past to present. The early schools of Oberlin, Pestalozzi, and Froebel are explored and focus is later placed on the past and the present Canadian/Quebec kindergarten system. Personal narratives from the classroom mark the conclusion of each section. These reflections encompass the overall emphasis of each segment by providing a look into the daily life of my teaching, hoping to bridge theory and practice.